Grazing incidence X-ray diffraction measurement of silver nanoparticles in metal-assisted etching of silicon. Issue 3 (September 2020) - Tang, Yunhui; Wang, Bo; Xue, Rui; Yan, Hui
Abstract : Silicon nanowires (SiNWs) were fabricated in a metal-assisted chemical etching method with two steps including dipping silicon wafers in AgNO3 /HF solutions and then in H2 O2 /HF solutions. Grazing incidence X-ray diffraction measurements with a set of incidence angles were carried out on the resulting samples to detect characteristics of silver nanoparticles in the etched silicon. Compared with the uniform size of silver nanoparticles on the surface, the silver nanoparticles in etched silicon were found with size increasing and content decreasing corresponding to the depths. Based on the silver size increasing phenomenon, a detailed supplementary hypothesis about SiNWs formation was proposed about silver disintegration and redeposition in the later stage of silicon etching. For 2, 3, 4, and 8 mM AgNO3 solutions used to study their effect on the SiNWs, it was found that a higher quantity of Ag + concentration such as 8 mM were not beneficial for producing good quality SiNWs.